Exploring Reading Comprehension and Speed: A Study of SMAN 1 Mojo Students - Lestari, Nurul Dwi; Azizah, Syafrinnissa; Lailiyah, Siti; Yulaikha, Siti (Indonesian Journal of Multidisciplinary Educational Research, 2023)
The problem being analyzed during this research is dissimilarity in the effective reading ability between one student and others and the factors that affect the effective reading speed. The method used was a case study method combined with a quantitative methodology. Twenty-seven students were involved as the research subjects. The data were obtained from observation text entitled "D'topeng Museum Angkut" read by the students. The process of calculating reading time was calculated independently by the students using a stopwatch. The results showed that (1) the average reading speed of the students was in the moderate or sufficient speed category; (2) the reading speed per student was in the adequate category (250 – 350 wpm). Even three students were in the effective category (above 350 wpm); and (3) concentration was one of the factors that influenced the effective reading speed. It can be concluded that in the analysis of the effective reading speed in class XI IPS 1 at SMAN 1 MOJO, the students had a moderate or adequate reading speed.